Juror Perceptions of the Legitimacy of Legal Authorities and Decision Making in Criminal Cases. Issue 4 (7th September 2012) - Farrell, Amy; Pennington, Liana; Cronin, Shea
<x xml:space="preserve">Abstract</x> Literature on trust in legal authorities and institutions demonstrates that trust affects individual behavior, yet there is little research on whether attitudes toward legal authorities such as the police or courts influence juror behavior as a third party assessing evidence and determining legal outcomes for others. Additionally, the literature on juror decision making confirms that juror race is an important predictor of juror decisions, but explanations for differences among racial groups are not clear. Since minority groups hold less favorable attitudes toward legal authorities generally, legitimacy theory may help explain racial differences in decision making among jurors. Using data from nearly 2, 000 jurors in felony trials, this research utilizes multilevel modeling techniques to find that jurors' trust in legal authorities is related to juror outcomes, though the effect of juror trust and confidence in the police is opposite that of juror trust and confidence in the courts. Additionally, juror race conditions the effect of trust in police and courts. Trust is a stronger predictor of both perceptions of evidence and voting for black jurors than it is for white jurors.